Soursop (Annona Muricata, Linn) Leaf Ethanol Extract Cream Application Affected the Expression of TNF-Î± and VEGF on Balb/C Mice Skin Exposed to Acute UVB - Susanto, Agus; Nasihun, Taufiqurrachman; Hussaana, Atina (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2018)
Background: Wound healing problems are often associated with TNF-Î± and VEGF expressions. However, the benefits and effects of ethanol extract cream from soursop leaves towards TNF-Î± and VEGF expression for burns healing process are yet to be known.Â Objective: To evaluate the benefits and influence of ethanol extract cream from soursop leaves in decreasing TNF-Î± expression and stimulate VEGF expression in BALB/c mice exposed to acute UVB radiation.Â Method: This study is a laboratory-based experimental study with post test only control group design. The subjects were 48 BALB/c female mice, divided into 24 subjects for TNF-Î± and 24 for the VEGF group, and were randomly distributed into 4 groups in each study, with each group containing 6 BALB/c mice. Group K was smeared with a base cream of 0.3 grams three times daily, while P1, P2 and P3 groups were each applied 0.3 grams of ethanol extract with consecutive consentrations of 2.5%, 5%, and 10% three times daily. On the sixth day, termination was performed on 24 mice to assess Tnf-Î± expression and on the eighth day also termination on 24 mice to assess VEGF expression. Preparation of substances was done using IHC method, analyzed using Kruskal Wallis test followed by Mann Whitney test.Results: The results of TNF-a and VEGF expression analysis based on Kruskal Wallis test obtained a p value of 0.0001 (p<0.05) showing that the mean expression of TNF-a and VEGF among the four groups ware significantly different. Mann Whitney test results revealed that the differences in expression of TNF-a and VEGF between the two groups were all significant differences (p<0.05). The mean TNF-a expression in the three treatment groups (PI, PII, PIII) ware significantly lower than the control group. The mean TNF-a expression in the PII and PIII treatment groups ware significantly lower than in the PI group, and the mean TNF-a expression in the PIII treatment group was significantly lower than the PII group. The mean VEGF expression in the three treatment groups (PI, PII, PIII) ware significantly higher than the control group. The mean VEGF expression in the PII and PIII treatment groups ware significantly higher than the PI group, and the mean VEGF expression in the PIII treatment group was significantly higher than in the PII group.Conclusion: Ethanol creams made of soursop leaves extract is proven to be useful and decreasing TNF-Î± expression and increase VEGF expression in BALB/c mice exposed to acute UVB rays.Keywords: Ethanol cream of soursop leaves extract, TNF-Î± expression, VEGF expression